Serum 5‐S‐cysteinyldopa behavior in the early phase of nivolumab treatment of 12 melanoma patients. Issue 11 (25th August 2018) - Omodaka, Toshikazu; Minagawa, Akane; Uhara, Hisashi; Wakamatsu, Kazumasa; Koizumi, Tomonobu; Yokokawa, Yoshiharu; Koga, Hiroshi; Okuyama, Ryuhei
Abstract: Along with the expansion of therapeutic options for metastatic melanoma, the development of useful biomarkers is urgently required to predict and monitor treatment response. Serum 5‐ S ‐cysteinyldopa (5‐ S ‐CD) has been identified as a diagnostic marker of malignant melanoma, but its utility as a biomarker for emerging therapeutic agents remains unknown. We assessed serum 5‐ S ‐CD in 12 metastatic melanoma patients (median age, 76 years; six men and six women) who had been treated with nivolumab (Nivo) at Shinshu University Hospital between 2014 and 2016. Serum 5‐ S ‐CD and lactate dehydrogenase levels before and at 3–6 weeks of Nivo treatment were obtained and their changes were compared with clinical responses as defined by the Response Evaluation Criteria in Solid Tumors criteria (version 1.1). A decrease of 10 nmol/L or more of serum 5‐ S ‐CD was observed only in partial response patients (2/3 cases, 67%), while an increase of 10 nmol/L or more of serum 5‐ S ‐CD was witnessed only in progressive disease patients (4/8 cases, 50%). Serum 5‐ S ‐CD changes were within ±10 nmol/L in the remaining six patients (partial response, one; stable disease, one; progressive disease, four). The results of the four moderately affected progressive disease patients were suspected to have been influenced by small‐sized metastatic lesions, a mixed response that included diminished and enlarged metastatic lesions, prior therapy to Nivo with BRAF inhibitors or radiation, or the development of brain metastasis. Serum 5‐ S ‐CD in the early phase of Nivo treatment may be helpful to predict therapeutic response in metastatic melanoma.